Pengujian Cone Penetration Test (SONDIR), di Gereja MRII Kota Ambon - C. G. Buyang; M. R. Ayal (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2024)
Soil testing is very important in the development planning process, especially to assess the strength and stability of the soil as a foundation base. Improper soil conditions can result in structural damage to buildings. Therefore, soil testing is necessary to provide optimal foundation recommendations, ensuring the safety and sustainability of the building. This information is needed to provide recommendations for appropriate foundations, especially in the context of church construction which often has large and heavy structures. This research aims to evaluate the characteristics of the land around the MRII Church in Ambon City with a focus on the use of sondir technology. This activity covers the importance of a deep understanding of the physical properties of soil in the context of planning and construction of church buildings. The testing method involves the use of mechanical sondir to measure soil characteristics and map subsurface geological structures. Test results show significant variations in characteristics around the church location, with the possibility of rock layers or geological changes that have the potential to affect the construction of the church building and surrounding infrastructure. Based on factual data and sondir testing (CPT) in the field, a drilled pile type foundation is recommended. However, the recommended results can be changed or supplemented with other technical information/data considering that sondir testing cannot directly show the condition of soil layers. It is best to carry out further testing with Hand Boring, NSPT Drilling and laboratory testing to obtain more accurate soil conditions and supporting parameters.